Risk of Parkinson's disease in patients with hypothyroidism: A nationwide population-based cohort study. (May 2020) - Chen, Shih-Fen; Yang, Yu-Cih; Hsu, Chung-Y; Shen, Yu-Chih
Abstract: Introduction: Hypothyroidism has been implicated in many other disease conditions, including neurodegenerative diseases. Parkinson's disease (PD) is one of the most common neurodegenerative diseases. The purpose of this study was to investigate the risk of PD in patients with hypothyroidism. Methods: A total of 4725 patients with hypothyroidism and 4725 controls (without hypothyroidism) matched by age, gender, index year, and Charlson Comorbidity Index (CCI) score were enrolled between 2000 and 2012. Patients were then followed until the end of 2013 using Taiwan's National Health Insurance Research Database, at which time participants who developed PD were identified. Cox regression analysis was used to calculate the hazard ratio (HR) with a 95% confidence interval (CI) of PD incidence rate between patients with hypothyroidism and unaffected controls. Results: Patients with hypothyroidism had a significantly increased risk of PD compared with unaffected controls (2.00 versus 1.10 per 1, 000 person-years, HR: 1.77, 95% CI: 1.13–2.76) after adjusting for age, gender, CCI score, physical comorbidities (brain injury, cerebrovascular disease, hypertension, dyslipidemia, and diabetes mellitus), and duration of levothyroxine use. Also, older age (≥50 vs. <50 - HR:14.83), higher CCI score (CCI score 1–2 & ≥3 vs. 0 - HR: 1.66–1.74), and specific comorbidities (brain injury (HR: 1.78) and cerebrovascular disease (HR: 2.46)) significantly increased the risk of PD after adjusting for the variables mentioned above. Conclusions: Patients with hypothyroidism have an increased risk of developing PD. Other prospective studies that take into account genetic vulnerability and environmental exposures are warranted to confirm their relationship. Highlights: Patients with hypothyroidism had a significantly increased risk of Parkinson's disease (PD). Older age, and more comorbidities significantly increased the risk of PD. Specific comorbidities (brain injury and cerebrovascular disease) would increase the risk of PD.